ASEAN Member States Responses to the Russian Invasion of Ukraine - Aulia Asri (Jurnal Mengkaji Indonesia, 2023)
Abstract: The military aggression that occurred on February 24, 2022, triggered a global crisis that certainly impacted the Southeast Asian region in various fields such as economics, politics, and security. ASEAN as an international organization in the region has made a statement to seek peaceful dialogue and urge a ceasefire so that military aggression in Ukraine can find a peaceful way and reduce civilian casualties and losses. Purpose: To find out the response of ASEAN members to Russia's military aggression against Ukraine. Design/Methodology/Approach: Data was collected through a literature study of previous works and official documentation from ASEAN and its member states. From this research, it can be seen how each ASEAN member country responds to Russia's military aggression invasion of Ukraine. In addition, this research also comparatively describes the responses of the ASEAN members. Findings: The comparison of ASEAN member states responses to Russia's military aggression against Ukraine varies. Some condemned the military aggression such as Indonesia, Singapore, and Malaysia. Some only did not respond or were neutral such as Laos, Thailand, and Vietnam. Some support the military aggression, such as Myanmar. The difference in response is due to the national political interests of each country. Originality/Value: This study focuses on ASEAN member countries that responded to Russia's military aggression against Ukraine, so the author believes that no one has studied with the same focus as this research.